1997
DOI: 10.1007/s11745-997-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of docosahexaenoic acid on mouse mitochondrial membrane properties

Abstract: Long-chain polyunsaturated (n-3) fatty acids have been proposed to be involved in a wide variety of biological activities. In this study, mitochondrial docosahexaenoic acid (DHA) levels were increased by either dietary manipulation or by fusing the mitochondria with phospholipid vesicles made from 1-stearoyl-2-docosahexaenoyl-sn-glycero-3-phosphocholine (18:0/22:6 PC). The fused mitochondria exhibited a DHA-induced decrease in respiratory control index (RCI) and membrane potential and an increase in proton mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 65 publications
5
71
0
1
Order By: Relevance
“…For example, Treen et al [64] were unable to see a difference in "fluidity" (fluorescence polarization of DPH and TMA-DPH) with intact Y-79 retinoblastoma cells cultured in DHA-enriched media despite observing a 4 to 5 fold increase in cellular DHA levels. Employing a different fluorescence method, several reports have indicated DHA does increase "fluidity" as assayed by probes sensing lateral mobility [60,64,65]. These observations are consistent with the hypothesis that DHA may play a major role in membrane lateral domain structure (discussed below).…”
Section: "Fluidity"supporting
confidence: 72%
See 2 more Smart Citations
“…For example, Treen et al [64] were unable to see a difference in "fluidity" (fluorescence polarization of DPH and TMA-DPH) with intact Y-79 retinoblastoma cells cultured in DHA-enriched media despite observing a 4 to 5 fold increase in cellular DHA levels. Employing a different fluorescence method, several reports have indicated DHA does increase "fluidity" as assayed by probes sensing lateral mobility [60,64,65]. These observations are consistent with the hypothesis that DHA may play a major role in membrane lateral domain structure (discussed below).…”
Section: "Fluidity"supporting
confidence: 72%
“…In agreement, fluorescence measurements on lipid bilayers confirmed that water content in the bilayer hydrocarbon region increases with double bond content [53]. Increases in mitochondrial permeability have also been linked to DHA content [65,81]. The resultant proton leakage in turn decimates the essential trans-membrane H + gradients, an event linked to mitochondrial-linked apoptosis [82] (see below).…”
Section: Permeabilitymentioning
confidence: 58%
See 1 more Smart Citation
“…It is conceivable that relocation of PC-TP to mitochondria increases the amount of 16:0/PUFA-PC species in the mitochondrial membranes. The ensuing increase of membrane fluidity is reported to generate a number of responses, such as the enhancement of membrane-associated phospholipase A 2 activity [43], proton leakage [44,45], and Ca 2ϩ efflux [46]. Furthermore, changes in phospholipid fatty acid composition can alter the activity of carnitine palmitoyltransferase I [47,48] and of the pyruvate carrier [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…More direct support for the hypothesis is provided by the experimental manipulation of membrane phospholipids, which shows that various mitochondrial properties, as well as the activity of Na þ -K þ -ATPase, are altered predictably through specific changes in FA composition [4,20,21]. The mechanisms responsible for activation of the membrane proteins remain unknown, but double bonds constrain rotation between carbons and cause kinks in the acyl chains.…”
Section: Introductionmentioning
confidence: 97%